Pengaruh Customer Bonding Terhadap Perilaku Pelanggan di UD. Tani Andalan Sipirok Kabupaten Tapanuli Selatan - Fithra Maharani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The purpose of this research is to determine the influence of customer bonding on customer behavior. The population of this study was 300 people at UD. Tani Andalan Sipirok, South Tapanuli Regency. The sampling was not random and the sample size was 30 people. Data analysis uses data validity tests, data reliability tests, simple regression tests and hypothesis tests, determination tests. Based on the Simple Linear Regression Test, the equation Y = 7.346 + 0.703 is obtained as follows: a constant of 7.346, meaning that if the Customer Bonding (X) value is 0, then the total Customer Behavior (Y) value is positive, namely 0.703, the X coefficient = 7.346. And the results of the t test show that the t-calculated value of the Customer Bonding variable (X) is 6.759, and the t table value is 1.701, so t calculated > t table (6.759 > 1.701) so it can be concluded that the Customer Bonding variable has a positive and significant effect on Customer Behavior (Y ) in UD's business. Tani Andalan Sipirok, South Tapanuli Regency. So H0 is accepted because t count > t table (6.759 > 1.701). Based on the test results using the Coefficient of Determination Test, a coefficient of determination value of 0.620 was obtained, that Customer Bonding (X) was able to explain 62.0% of changes in Customer Behavior (Y) in UD businesses. Tani Andalan Sipirok, South Tapanuli Regency. Meanwhile, the remaining 38.0% is explained by other factors that were not examined by researchers. The results of this research show that customer bonding has an influence on customer behavior which is expressed by the calculation results of t count > t table, namely 6.759 > 1.701 so it can be concluded that t count is in the rejection of H0 and Ha is accepted. Based on the Determination test, the R Square value is 0.620 or 38.0% of the customer behavior variable (Y) is influenced by customer bonding (X).